THE IMPLEMENTATION PROCESS OF MARGONDANG IN BATAK ANGKOLA WEDDING CEREMONY: SEMIOTICS APPROACH - Muhizar Muchtar; Mayasari Mayasari (Institut Pendidikan Tapanuli Selatan, 2023)
The purpose of this research is to provide understanding to the readers and increase their knowledge about the Margondang process in Batak Angkola wedding, so that they can easily understand it. Researchers analysed using the theory of Sudaryanto (2015). The analysis in this study uses qualitative research methods. To support the analysis, researchers used books, journals and theses. Researchers obtained the data from videos and photos.